Review on hand gesture recognition - Bilal, Sara Mohammed Osman Saleh; Akmeliawati, Rini (IIUM Press, 2011)
The aim of this chapter is to present a review on the development of vision systems based on hand gesture. Vision-Based Human to Computer Interaction (HCI) systems has the ability of carrying a wealth of information in a natural way and at a low cost. Therefore hand recognition becomes a widely studied topic with a wide range of applications such as SL translators, gesture recognition for control, augmented reality, surveillance, medical image processing, and etc. Hand recognition with no constraint on the shape is an open issue because the human hand is a complex articulated object consisting of many connected parts and joints. Considering the global hand pose and each finger joint, human hand motion has roughly 27 degree offreedom (DOF)